Dự đoán hoạt tính kháng Hemozoin của các chất từ thư viện VICB và MMV Malaria Box bằng phương pháp In Silico / Kim Ngọc Sơn, Trương Văn Đạt, Nguyễn Tiến Huy, Nguyễn Thụy Việt Phương - Kim, Ngọc Sơn
With regard that in development of new mechanisms or novel anti-malarial compounds to control antimalarial drug resistance and eliminate malaria, hemozoin formed by hemoglobin degradation of Plasmodium falciparum as the unique heme detoxification pathway, is known as a novel potential target for antimalarial drug discovery, … this study was aimed to predict anti-hemozoin activity from the VICB library and the MMV Malaria Box using in silico approach. A total 75 compounds from VICB library and the MMV Malaria Box as hemozoin inhibitors were collected for building a 2D-QSAR model using partial least square algorithm in MOE package. This 2D-QSAR model was successful built with the predictive parameters R2 = 0.79, and RMSE = 0.1. Subsequently, the model was applied to predict anti-hemozoin activity for 18560 compounds from Traditional Chinese medicine database after selecting through Lipinski 5 rules. As predictive results, 3233 compounds showed having the IC50 ≤ 10 µM, and the terpenoid compounds potential antimalarial agents. These results might be useful for designing new hemozoin inhibitors in development of new antimalarial drugs.